Another "D" in MUDPILES? A Review of Diet-Associated Nondiabetic Ketoacidosis - Waqas Ullah; Mohsin Hamid; Hafez Mohammad Ammar Abdullah; Mamoon Ur Rashid; Faisal Inayat (SAGE Publishing, 2018)
Ketogenic diet or very-low-carbohydrate diet gained widespread popularity in the 1990s due to their favorable effects on weight loss and diabetes among others with good short-term safety data. People on ketogenic diets exist in a state of "dietary ketosis" in which the body production of ketone is equal to consumption and no harmful effects of ketonemia occur. However, in face of stress, the harmless "dietary ketosis" can lead to profound acid-base disturbances due to massive overproduction of ketone bodies that overwhelms the acid buffer system of the body. A handful of case reports have been published on this topic calling the safety of ketogenic diet into question. In this article, we chronicle a unique case of ketogenic (Atkins) diet-associated ketoacidosis, and we present a comprehensive literature review on the etiology of ketoacidosis.